La didactique du plurilinguisme au service de la médiation : comment recourir aux ressources du répertoire langagier des apprenants en classe de FLE lors des activités de médiation ? - Kucharczyk Radosław (Recherches en didactique des langues et des cultures)
The aim of our article is to reflect on the potential marriage between plurilingual competence and mediation activities. The aim of the research, the results of which we will present in the article, was to examine how Polish-speaking students learning FLE (level B1) as a second foreign language proceed during mediation activities. The classroom survey enabled us to collect data on the techniques used by learners (quantitative analysis), while the individual semi-directive interviews gave us access to the strategies that the learners surveyed resorted to during the task. The aim of this retrospection was to examine the cognitive means students used to access the resources in their language repertoire.